Soul of society a focus on the lives of children & youth - Warehime, M. Nicole (Bingley, U.K. : Emerald, 2014)
As social scientists, we are called to investigate society. A powerful component of understanding society can be found when researching the lives of children and youth. "There can be no keener revelation of a societys soul than the way in which it treats its children"stated Nelson Mandela. This volume provides a glimpse into the lives of children and youth; thus, The Soul of Society: A Focus on the Lives of Children and Youth.
Youth experiences of space in a gentrifying community : a case study of Asbury Park, New Jersey / Alicia Raia-Hawrylak -- Poetic perspective, critical insight : a study of youth attitudes toward place and community / Maggie La Rochelle, Patsy Eubanks Owens -- Children's participation in communication systems : a theoretical perspective to shape research / Claudio Baraldi -- The role of children and youth in teaching student teachers how to teach / Patricia Danyluk -- Gender differences in the effects of teen employment upon adolescents educational and occupational aspirations / Sampson Lee Blair, Patricia Neff Claster -- Rising souls : religion and family relationships among Latino adolescents / Eve Veliz -- Sexualisation and the discursive figure of the child / Jessica Clark -- A cross-cultural study of children's understanding of terrorists : "They make the world not safe" / Maureen Blankemeyer, Kathleen Walker, Mary Dellmann-Jenkins -- Exploring the links between victimization and delinquency among Caribbean youth : using an ecological perspective to review the literature / Julie V. Xavier -- Exposure to online hate among young social media users / Atte Oksanen ... [et al.].
Print version record
Keywords: Social Science -- Children's Studies; Social Science -- Sociology -- General; Social Science -- Sociology / Marriage & Family; Sociology: family & relationships; Age groups: children; Cultural studies; Child welfare; Social work with youth